Teaching with heart : (Jossey-Bass, 2014)
Each and every day teachers show up in their classrooms with a relentless sense of optimism. Despite the complicated challenges of schools, they come to and remain in the profession inspired by a conviction that through education they can move individuals and society to a more promising future. In Teaching with Heart: Poetry that Speaks to the Courage to Teach a diverse group of ninety teachers describe the complex of emotions and experiences of the teaching life - joy, outrage, heartbreak, hope, commitment and dedication. Each heartfelt commentary is paired with a cherished poem selected by the teacher. The contributors represent a broad array of educators: K-12 teachers, principals, superintendents, college professors, as well as many non-traditional teachers. They range from first year teachers to mid-career veterans to those who have retired after decades in the classroom. They come from inner-city, suburban, charter and private schools. The teachers identified an eclectic collection of poems and poets from Emily Dickinson, to Richard Wright, to Mary Oliver to the rapper Tupac Shakur. It is a book by teachers and for all who teach. The book also includes a poignant Foreword by Parker J. Palmer (The Courage to Teach), a stirring Introduction by Taylor Mali (What Teachers Make), and a moving Afterword by Sarah Brown Wessling (Teaching Channel). Where Teaching with Fire honored and celebrated the work of teachers; Teaching with Heart salutes the tenacious and relentless optimism of teachers and their belief that despite the many challenges and obstacles of the teaching life, much is possible